The Implementation Of Listen, Read, And Discuss (LRD) Strategy To Improve Students’ Reading Comprehension In Recount Text - Nur Syafira; Nur Fauzia (Jurnal Pendidikan dan Sastra Inggris, 2023)
Enhancing reading comprehension is essential for comprehending and acquiring proficiency in the English language. To improve students' understanding of reading comprehension skills, it is essential to employ an appropriate learning method during the learning process. Thus, this study employed the LRD strategy as a method for acquiring knowledge. The aim of this study is to ascertain whether the implementaton of the LRD technique enhances students' reading comprehension in recount texts. Therefore, this study employed the quantitative approach, specifically a pre-experimental design. The study included 32 students from class VIII SMPN 33 Gresik. After that, pretest and posttest consisting of multiple-choice questions were used collecting the data for the study. As a result, the SPSS 25 Paired Sample T-test was utilized in this investigation concerning to conduct data analysis. The investigation revealed substantial findings when comparing pre-test and post-test. The pre-test provided a result of 54.69, while the post-test provided a result of 77.03. The 2-tailed significance analysis showed that the p-value of 0.00 is less than the significance level of 0.05. It indicates that there was a significant increase between the pre-treatment and post-treatment scores. According to these findings, students have the potential in improving their reading comprehension after implementing the LRD strategy.